TREATMENT OF RADIATION EXTERNAL FOR BRAIN METASTASIS WITH 3D-CRT WITHOUT USING MLC AT RADIOTHERAPY INSTALLATION OF KEN SARAS HOSPITAL - Nurul Fatimah MZ; Eko Kuntjoro; Darmini Darmini (Jurnal Imejing Diagnostik (JImeD), 2018)
Background: Brain metastases are common manifestations of malignancies that spread types of cancer such as breast cancer, lung cancer can spread to the brain. Radiotherapy in brain metastases is the chosen palliative treatment because it is considered less invasive. Purpose of this research is to know radiation, radiation optimization with 3D-CRT technique without using MLC at Ken Saras Hospital Radiotherapy Installation.Methods: This research is a qualitative research with case study approach. Data were collected in January-February 2018 at Ken Saras Hospital Radiotherapy Installation with observation, interview and documentation method with Radiation Oncology Specialist, Medical Physicist and Radiografer / Radiotherapist. Data obtained from the study were analyzed by interactive model, making the interview transcript subsequently reduced and processed in the form of open coding, presented in the form of quotations and then can be drawn conclusions.Result: The results showed that external radiation management on 3D-CRT brain metastasis technique without using MLC at Ken Saras Hospital Radiotherapy Installation included patient consultation, CT Simulator shooting images, contouring, medical physics planning and radiation verification and treatment. Optimization of brain metastases radiation without using MLC is done by using gantry and collimator variations.Conclusion : Brain metastases with 3D-CRT technique without using MLC at the Hospital Radiotherapy Installation including patient consultation, CT Simulator firing, medical physics planning then verification and radiation treatment. Optimization of brain metastases with 3D-CRT technique without MLC at Ken Saras Hospital's Radiotherapy Installation can be done using a variety of gantry and collimator variations.